Pengaruh Kemasan Metalized Terhadap Perubahan Sifat Fisik dan Kimia Sup Labu Kuning Instan - Ica Clarissa; Nurrahman .; Agus Suyanto (Universitas Muhammadiyah Semarang, 2026)
Pumpkin has physical and chemical properties that support it to be processed into instant soup. However, these properties can change during storage, so optimal packaging is needed to protect the product from damage and extend its shelf life. One of the commonly used packaging for instant soup is metalized packaging. The purpose of this study was to determine the physical and chemical changes of instant pumpkin soup in metalized packaging during storage. Pumpkin processed into instant soup, then packaged using metalized packaging was stored at temperatures of 27, 37, and 47℃ for 28 days. Observations were made on hygroscopicity, value, β-carotene content, and vitamin C content every 7 days. The results showed that the interaction treatment of temperature and storage time had a very significant effect on hygroscopicity, value, β-carotene content, and vitamin C content during storage. The best temperature for storing instant pumpkin soup is 27℃ with a shelf life of 1142.43 days